2018
DOI: 10.1007/s00405-018-4956-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic values of hematological biomarkers in nasopharyngeal carcinoma patients treated with intensity-modulated radiotherapy

Abstract: PurposeIn this study, we evaluated the prognostic values of hematological biomarkers in primary nasopharyngeal carcinoma (NPC) patients receiving definitive intensity-modulated radiotherapy (IMRT).MethodsThere were 427 NPC patients enrolled between January 2010 and March 2013 at Fudan University Shanghai Cancer Center. Pre-treatment absolute neutrophil count (ANC), platelet count (APC), lymphocyte count (ALC), neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) were collected as prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…ROC curves were used to estimate the optimal NLR cut-off value in 14 studies. [10,2224,2729,32,35,39,4144] Majority included all or locally advanced stages, while 2 studies focused only on early stage cancer. [23,44]…”
Section: Resultsmentioning
confidence: 99%
“…ROC curves were used to estimate the optimal NLR cut-off value in 14 studies. [10,2224,2729,32,35,39,4144] Majority included all or locally advanced stages, while 2 studies focused only on early stage cancer. [23,44]…”
Section: Resultsmentioning
confidence: 99%
“…This analysis indicated that NLR and PLR were useful and cost-effective predictors that could be applied to inform more precise treatment strategies. 13 However, although a number of predictors have been identified in the past few decades, few epigenetic predictors have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Ye et al . reported that both high NLR and PLR were correlated with poor survival in patients of nasopharyngeal carcinoma . A meta‐analysis by Yodying et al .…”
Section: Discussionmentioning
confidence: 99%